Bioinformatics based exploration of the anti-liver fibrosis mechanism of Pien Tze Huang via EGFR/JAK1/STAT3 pathway - Hong, Xiaoting; Ye, Yonghua; Lin, Chunfeng; Zheng, Miaolan; Lin, Fan; Xiong, Qing; Xu, Wei; Li, Huang; Zhang, Yuqin; Zheng, Haiyin (Frontiers in Immunology, 2025)
ObjectLiver fibrosis is a key stage in chronic liver disease, but targeted treatments are scarce. Pien Tze Huang (PZH), a traditional Chinese medicine, shows anti-fibrotic potential, though its mechanisms are not fully understood.MethodA liver fibrosis model was created in C57BL/6 mice using carbon tetrachloride (CCL4). PZH’s effects were assessed via liver morphology, serum/liver biomarkers, transaminase levels, and histopathology. PZH’s chemical components were identified through database and literature research. Network pharmacology, molecular docking and molecular dynamics simulation were used to investigate the underlying mechanisms, which were validated in vivo and in vitro with immunofluorescence and Western blot analyses.ResultsPZH significantly attenuated hepatic transaminase disorders, reduced serum procollagen III/IV, alleviated fibrotic liver histopathology, and suppressed macrophage markers and hepatic inflammation. Through multi-database integration, 24 bioactive compounds were identified in PZH, including ginsenoside Rh2. Further investigation showed that PZH ameliorates liver fibrosis by modulating key targets, including AKT1, EGFR, and STAT3. Molecular docking analysis and molecular dynamics simulation demonstrated a significantly high binding affinity between ginsenoside Rh2 and the target proteins EGFR, JAK1, and STAT3. In vitro and in vivo experiments confirmed that PZH and ginsenoside Rh2, reduced RAW264.7 inflammatory mediators, inhibited M1 polarization, and downregulated EGFR/JAK1/STAT3.ConclusionThe findings reveal that PZH ameliorates liver fibrosis by inhibiting macrophage-mediated inflammation via blockade of the EGFR/JAK1/STAT3 signaling axis, providing a mechanistic foundation for its clinical application.